Effect of Working Current on C12A7 Hollow Cathode - Yajun Huang; Xiaoxian Wang; Guomin Cui; Pingyang Wang; Dongsheng Cai (Aerospace, 2023)
The C12A7 hollow cathode is expected to usher in a new generation of hollow cathodes because of its low work function and chemical stability. In order to reduce the emission melting and degradation caused by the overheating of this new cathode, different working currents of the C12A7 hollow cathode were studied in this work. The working currents ranged from 1 A to 20 A. The results show that the C12A7 hollow cathode works well under the condition of a low current, but it is unstable under high current condition. A simulation with the COMSOL internal working environment showed that enlarging the cathode orifice size is beneficial to reduce the risk of overheating of the electride emitter. The C12A7 hollow cathode shows a voltage transition phenomenon under a high operating current. The plasma plume state at the cathode outlet gradually changes from bright violet to dark yellow. The emitter also melts at high temperatures under high-current conditions. Its short lifetime makes the C12A7 hollow cathode difficult to apply in practical application scenarios under high-current conditions.